2020
DOI: 10.1007/s00249-020-01487-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-embedded TSPO: an NMR view

Abstract: Translocator Protein (18 kDa) (TSPO) is a mitochondrial transmembrane protein commonly used as a biomarker for neuroinflammation and is also a potential therapeutic target in neurodegenerative diseases. Despite intensive research efforts, the function of TSPO is still largely enigmatic. Deciphering TSPO structure in the native lipid environment is essential to gain insight into its cellular activities and to design improved diagnostic and therapeutic ligands. Here, we discuss the influence of lipid composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Hence, in liposomes, mTSPO is stabilized but only in monomers and using both cholesterol and a stabilizing ligand [42], confirming that mTSPO, as shown by solid state NMR, is instable in liposomes except in presence of ligand [43]. As well, long chain lipids or lipid mixture can stabilize mTSPO but not better than DMPC lipid and the presence of the ligand remains essential [44].…”
Section: Characterization Of Mtspo-dpc Complex By Sec-sansmentioning
confidence: 53%
“…Hence, in liposomes, mTSPO is stabilized but only in monomers and using both cholesterol and a stabilizing ligand [42], confirming that mTSPO, as shown by solid state NMR, is instable in liposomes except in presence of ligand [43]. As well, long chain lipids or lipid mixture can stabilize mTSPO but not better than DMPC lipid and the presence of the ligand remains essential [44].…”
Section: Characterization Of Mtspo-dpc Complex By Sec-sansmentioning
confidence: 53%
“…While the atomic structure of monomeric mTSPO bound to the high-affinity PK11195 ligand has been determined by solution NMR in DPC detergent micelles [20], ssNMR studies have revealed the dynamic monomer-dimer equilibrium of mTSPO complexed with DAA1106 ligand in DMPC lipids regulated by diamagnetic [23] or paramagnetic [65] cholesterol, another ligand. Rivière et al [24] studied the influence of 1,2-dinervonoyl-sn-glycero-3-phosphocholine (with an acyl chain monosaturated and longer than DMPC) or a mix of lipids but no resolution improvement of the TSPO/cholesterol 13 C - 13 C correlation spectra of the was observed for the protein reconstituted in the new membrane mimics. Cholesterol is also a key structural element of mitochondrial membrane and its concentration in the cell membrane varies between 30 and 50 % mole/mole of the entire lipids compounds.…”
Section: Discussionmentioning
confidence: 99%
“…When reincorporated in liposomes, the mTSPO exhibits high affinities for its ligands like PK11195 and cholesterol [22], and ssNMR studies have shown that cholesterol mediates allosteric regulations of the ligand bound protein [23]. In 2021, Rivière et al explored by ssNMR the impact of three different lipid composition on the structure of mTSPO embedded into lipid bilayers in the presence and in the absence of the ligand and further confirmed how cholesterol can affect the tertiary and quaternary mTSPO structure [24]. Despite these efforts, detailed high-resolution atomic data of mTSPO in its native-lipid environment without ligand, that would permit to directly characterize the structural changes mediated by ligand binding that are linked to TSPO functional properties, are still missing.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although most of the direct isolation of membrane protein studies used bacteria, the use of mammalian and other cell types and other organisms such as viruses, insects, and fungi will become common in the near future. It would be exciting to explore the use of the nanodiscs technology for other membrane-related studies as well [ 67 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 ].…”
Section: Conclusion and Future Scopementioning
confidence: 99%